Descriptive Paraphilic Behaviors in the General Non-Clinical Population in Puerto Rico - Fankhanel, Edward; Esteban, Caleb; Berrios, Jorge; Figueroa, Frances; Santos-Gómez, María del C.; Rivera-Segarra, Eliut (Revista Caribeña de Psicología, 2021)
The objectives of this study were: 1) describe paraphilic sexual activities in Puerto Rico, identifying differences between fantasies, urges, or behaviors of specific paraphilias, 2) explore if there are relations between sexual fantasies and acting out (behavior) those fantasies, 3) explore the satisfaction with their lives, mental health and worries about the sexual behavior of those who report paraphilic behaviors, and 4) describe the feelings during and after having atypical fantasies, desired and/or behavior. A total of 1,255 participants completed an online survey, including socio-demographics, specific sexual fantasies, urges and behaviors, and psychological variables. Participants were able to express interests between fantasies, urges, and behaviors in each paraphilic activity. Most participants had at least a college degree (78.2%), were Catholic (65%), and identify as Hispanic (86.3%). Results showed that most participants reported no sexual paraphilic activities. The most-reported activity was watching pornography, followed by partialism and voyeurism. Correlations analysis between sexual fantasies and behaviors showed a significant correlation between voyeurism with exhibitionism, frotteurism, watching your partner have sex with others, and watching pornography. These results provide new insight into the current paraphilic interests in the non-clinical population and should elicit interest in further studies.